An Emergy-based Assessment of the Impact of Dam Construction on River Ecosystem Service Values: A Case Study of the Three Gorges Dam - Liu, Chang; Liu, Gengyuan; Yang, Qing (Journal of Environmental Accounting and Management, 2026)
It is urgent to make a break through in methodology and construct a method to evaluate the impact of dam construction on the changes of river ecosystem service values. Taking Three Gorges Dam as an example, the service values of river ecosystem before and after dam construction are evaluated. The results show that the indirect services are the largest, followed by the direct services and the existing services. With respect to the direct services, the most signiﬁcant service value before and after dam onstruction is NPP increase. In terms of the indirect values, the material transportation service of the river is impaired after dam construction, but there is the addition of hydropower generation, which becomes one of the signiﬁcant river services. With respect to existing services, the climate regulation capacity of the river ecosystem is improved after dam construction; the service value is 2.74 times of that before dam construction. Though dam construction brings some positive effects, such as ﬂood control, it also leads to negative effects, such as land inundation. Comprehensively considering the positive and negative effects of dam construction,the total river ecosystem service value before dam construction is 4.82×1021 sej·yr−1, while the total river ecosystem service value after dam construction is 7.65×1021 sej·yr−1, which has increased by 58.79% than before, indicating that there is an overall positive impact of dam construction, and the overall service value of the river ecosystem is enhanced.